The 'too muchness' of excitement: Sexuality in light of excess, attachment and affect regulation. (20th February 2015) - Benjamin, Jessica; Atlas, Galit
Abstract : This paper brings together contemporary thinking about early attachment and affect regulation with our clinical and theoretical understanding of the problems of adult sexuality. In addition to recent theories of affect regulation and attachment, we incorporate Laplanche's idea of 'excess', which was an important transitional concept integrating real experience with fantasy in sexuality. We elaborate the idea of excess –‐ 'too‐muchness' –‐ to illuminate the early overwhelming of the psyche that affects the formation of sexuality. Linked to recent theoretical developments, this idea helps to grasp the relationship between sexual excitement and early affect regulation, showing how excitement becomes dangerous, thus impeding or distorting desire. The 'too‐muchness' of excitement recalls the experience of being a stimulated, overwhelmed, unsoothed child and influences later inability to tolerate sexual arousal and the excitement affect. A clinical case illustrates this connection between attachment trauma, anxiety about sexuality, as well as shameful experiences of gender identity as an area of trauma. We emphasize the importance of working through the terrors and desires of the mother–baby relationship as they emerge in the transference–countertransference in order to develop the ability to hold excitement and stimulation without experiencing the too‐much as the intolerable. This includes the working‐through of ruptures related to overstimulation as well as the delicate balance of attention to fantasy and intersubjective work in the transference.